Green Synthesis of Cr-PTC-HIna Metal Organic Frameworks (MOFs) and Its Application in Methylene Blue Photocatalytic Degradation - Nur Mahrunnisa; Adawiah Adawiah; Isalmi Aziz; Agustino Zulys (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Metal Organic Framework (MOF) is a material that serves as a photocatalyst for decomposing methylene blue pollutant. MOF can be constructed using several kinds of synthetic methods. This study aims to determine the alternative efficient and eco-friendly synthesis method of isonicotinic acid-modulated chromium perylene 3,4,9,10-tetracharboxylate MOF (Cr-PTC-HIna) using solvothermal, hydrothermal, sonochemical, and mechanochemical methods. FTIR analysis revealed that Cr-PTC-HIna was successfully fabricated only by solvothermal, hydrothermal, and sonochemical methods, yielding 40.68%, 44.27%, and 46.50%. Cr-PTC-HIna-ST, Cr-PTC-HIna-HT, and Cr-PTC-HIna-SC have band gap energies of 2.02, 2.02, and 1.98 eV, respectively. Cr-PTC-HIna-HT and Cr-PTC-HIna-SC with irregular shapes form agglomerations. Cr-PTC-HIna-SC had the highest surface area, pore volume, and pore size of 92.76 m2.g−1, 0.3947cm3.g−1, and 142.74 nm, respectively. Cr-PTC-HIna-SC has the highest percentage of methylene blue decolorization through adsorption of 61.843% and photocatalytic degradation of 25.635%. Sonochemical and hydrothermal showed potential as more eco-friendly methods than solvothermal in synthesizing Cr-PTC-HIna MOF. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).